Improving uniform scattering device for straw-smashing, back-throwing, no-tillage planter under complete straw mulching condition - Gu, Fengwei; Gao, Xuemei; Wu, Feng; Hu, Zhichao; Chen, Youqing; Zhang, Chong (International Journal of Agricultural and Biological Engineering, 2018)
With the objective of obtaining a completely straw-mulched field, when no-tillage mechanical sowing is implemented with straw smashing, delivering, and back-throwing approaches, it may be difficult to scatter the smashed straw uniformly during a succeeding wheat sowing step. This is because the previous rice straw is substantial in quantity and has a high humidity and toughness, which may easily result in non-uniform straw mulching and thus sparse and weak seedlings of wheat. Therefore a force-dispersing and uniform-scattering device was designed. With the number of scattering impellers, impeller angle, and impeller rotation speed as the main factors and the percentage of pass for the scattering width and non-uniformity of the straw mulching as the assessment indices, single-factor experiments and orthogonal regressive tests were performed, and a dual-index (percentage of pass for the scattering width and non-uniformity of the straw mulching) fitted regression equation was established. The test results suggested that the main factors (from primary to secondary) that influence the indices were the impeller rotation speed, number of scattering impellers, and impeller angle. The optimal parameter combination for the uniform scattering device was four rows of impellers with an angle of 15°, rotation speed of 1015 r/min, percentage of pass of 72.65% for the scattering width, and a non-uniformity of 13.8% in the straw mulching. This combination can be used to realize a uniform scattering of the smashed straw along the seedling rows on the after-sowing ground. According to the field investigation of the wheat growth, the wheat emergence rate was 90.7%. The research results can provide a reference for improving the uniform scattering device for a straw-smashing, back-throwing, no-tillage planter for obtaining a completely straw-mulched field, enhancing the quality of the machinery operation, and ensuring good and strong seedlings after sowing.Keywords: complete straw mulching, no-tillage planter, uniform scattering of strawDOI: 10.25165/j.ijabe.20181106.4597Citation: Gu F W, Gao X M, Wu F, Hu Z C, Chen Y Q, Zhang C. Improving uniform scattering device for straw-smashing, back-throwing, no-tillage planter under complete straw mulching condition. Int J Agric & Biol Eng, 2018; 11(6): 49–57.